PENGARUH EKSPOR DAN UTANG LUAR NEGERI TERHADAP CADANGAN DEVISA DI INDONESIA TAHUN 2005-2019 - Abqori Irwandi Rhobi; Ekwarso Hendro; Widayatsari Any (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine the influence of exports and foreign debt on foreign exchange reserves in Indonesia. This study uses independent variables consisting of exports and foreign debt, with the dependent variable, namely foreign exchange reserves. The data used in this study are annual data from 2005- 2019. The analytical method used is descriptive quantitative with multiple linear regression OLS (Ordinary Least Square) approach which is processed using EViews version 10. The test results show that exports and foreign debt simultaneously have a significant effect on foreign exchange reserves in Indonesia. Meanwhile, exports have a positive and significant effect on foreign exchange reserves in Indonesia and foreign debt has a positive and significant effect on foreign exchange reserves in Indonesia. In addition, the value obtained from the adjusted R2 is 93.35%.Keywords: Foreign Reserves, Exports, Foreign Debt.